2000
DOI: 10.1073/pnas.97.21.11466
|View full text |Cite
|
Sign up to set email alerts
|

Selective CXCR4 antagonism by Tat: Implications forin vivoexpansion of coreceptor use by HIV-1

Abstract: Chemokines and chemokine receptors play important roles in HIV-1 infection and tropism. CCR5 is the major macrophage-tropic coreceptor for HIV-1 whereas CXC chemokine receptor 4 (CXCR4) serves the counterpart function for T cell-tropic viruses. An outstanding biological mystery is why only R5-HIV-1 is initially detected in new seroconvertors who are exposed to R5 and X4 viruses. Indeed, X4 virus emerges in a minority of patients and only in the late stage of disease, suggesting that early negative selection ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
305
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(328 citation statements)
references
References 50 publications
22
305
1
Order By: Relevance
“…Tat concentrations of 100 to 500 ng/ml had no cytotoxic effects on H69 cells or on C. parvum sporozoites and were selected for this study. The concentrations used throughout this study are consistent with the concentrations used in other studies in which workers examined physiological roles of Tat in tissues, where the localized Tat concentration is expected to be slightly greater than that detected in serum from HIV-infected individuals (2 to 40 ng/ml) (43,51).…”
Section: Methodssupporting
confidence: 72%
“…Tat concentrations of 100 to 500 ng/ml had no cytotoxic effects on H69 cells or on C. parvum sporozoites and were selected for this study. The concentrations used throughout this study are consistent with the concentrations used in other studies in which workers examined physiological roles of Tat in tissues, where the localized Tat concentration is expected to be slightly greater than that detected in serum from HIV-infected individuals (2 to 40 ng/ml) (43,51).…”
Section: Methodssupporting
confidence: 72%
“…Sequence prediction suggested that JM4 is a four-transmembrane-spanning protein with a preferential localisation at the endoplasmic reticulum (ER). JM4 shares sequence similarity with human JWA and the rat homologue glutamate transporter-associated protein [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], which regulates glutamate uptake by interacting with the ten-transmembrane-spanning excitatory amino acid carrier 1 (EAAC1) [16]. We show that JWA, like JM4, binds to CCR5.…”
Section: Introductionmentioning
confidence: 98%
“…Most importantly, the chemokine receptors CCR5 and CXCR4 have been identified as the two major co-receptors for the human immunodeficiency virus type 1, HIV-1, which infects CD4 + target cells [1][2][3][4][5][6]. CCR5 is expressed on memory T lymphocytes, macrophages, and dendritic cells and is mainly associated with transmission of viruses during primary infection [2], while CXCR4 seems to be important at later stages of the disease [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A small percentage of HIV-infected patients have detectable serum levels of Tat that are in the nanogram/ml range (63,64). However, this may be an underestimation of the actual levels because Tat may be sequestered in lymphoid tissues, for example (64).…”
Section: Fig 8 Inhibition Of Nf-b Activation By Adib␣srmentioning
confidence: 99%